“Pink power”—the importance of coralline algal beds in the oceanic carbon cycle - Nadine Schubert; Fernando Tuya; Viviana Peña; Paulo A. Horta; Vinícius W. Salazar; Pedro Neves; Cláudia Ribeiro; Francisco Otero-Ferrer; Fernando Espino; Kathryn Schoenrock; Federica Ragazzola; Irene Olivé; et al. (Nature Communications)
Abstract Current evidence suggests that macroalgal-dominated habitats are important contributors to the oceanic carbon cycle, though the role of those formed by calcifiers remains controversial. Globally distributed coralline algal beds, built by pink coloured rhodoliths and maerl, cover extensive coastal shelf areas of the planet, but scarce information on their productivity, net carbon flux dynamics and carbonate deposits hampers assessing their contribution to the overall oceanic carbon cycle. Here, our data, covering large bathymetrical (2–51 m) and geographical ranges (53°N–27°S), show that coralline algal beds are highly productive habitats that can express substantial carbon uptake rates (28–1347 g C m−2), which vary in function of light availability and species composition and exceed reported estimates for other major macroalgal habitats. This high productivity, together with their substantial carbonate deposits (0.4–38 kilotons), renders coralline algal beds as highly relevant contributors to the present and future oceanic carbon cycle.